2010
DOI: 10.1093/heapol/czq002
|View full text |Cite
|
Sign up to set email alerts
|

The response to flexibility: country intervention choices in the first four rounds of the GAVI Health Systems Strengthening applications

Abstract: Since December 2005 the GAVI Alliance (GAVI) Health Systems Strengthening (HSS) window has offered predictable funding to developing countries, based on a combined population and economic formula. This is intended to assist them to address system constraints to improved immunization coverage and health care delivery, needed to meet the Millennium Development Goals. The application process invites countries to prioritize specific system constraints not adequately addressed by other donors, and allows them to al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…This alignment notwithstanding, the actual measures proposed for action ignore important recommendations such as the need to address barriers at the level of leadership and governance and at the level of the financing system. The blindness of GAVI HSS proposals to the need to address issues related to the financing system has also been identified in a previous study 47 . This blindness to strategic gaps may reflect the challenges global health initiatives face in shifting from management through programs to managing through systems 50 .…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…This alignment notwithstanding, the actual measures proposed for action ignore important recommendations such as the need to address barriers at the level of leadership and governance and at the level of the financing system. The blindness of GAVI HSS proposals to the need to address issues related to the financing system has also been identified in a previous study 47 . This blindness to strategic gaps may reflect the challenges global health initiatives face in shifting from management through programs to managing through systems 50 .…”
Section: Discussionmentioning
confidence: 75%
“…The qualitative analysis was similar to the one described by Goeman et al 47 . It was based on WHO's health system building block categories -service delivery, health workforce, health information systems, logistics (medical products, vaccines and technology), financing and leadership & governance 48 .…”
Section: Content Analysis Of Documents and Of The Qualitative Data Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…31 All the Ministries of Health in the 2011 case study reported receiving specific health systems strengthening grants from the GAVI Alliance and/or Global Fund, releasing significant revenues for national health budgets. 26,32 Coordinating coordination in the new aid environment With the growing participation of agencies such as the GAVI Alliance and Global Fund, and their attempts to extend their engagement beyond their narrowly defined mandates, Ministry of Health staff and their WHO and UNFPA country office advisors were now grappling with a growth in mechanisms to coordinate this increasingly diverse field of development stakeholders and programmes. By 2011, all countries studied had faced requirements for new coordination structures: the PRSPs and reporting of MDG progress brought national stakeholders together; the GAVI Alliance made a health sector coordination committee a prerequisite for health systems strengthening funding; and the Global Fund had set up its own Country Coordinating Mechanism (CCM), often with overlapping, but not identical, membership.…”
Section: Resultsmentioning
confidence: 99%
“…(p. 1923) 22 GaVi has taken some tentative steps in recognizing this impasse through its Health Systems Strengthening window launched in 2006, but it needs to make this a priority. 10,23 fundamentally, using aMcs to supply vaccines to developing countries reflects an acceptance of the patent system as the best method for increasing vaccine coverage. We reject this position.…”
mentioning
confidence: 99%